The final days of Jesus, the thrill of defeat, the agony of victory : a classical historian explores Jesus's arrest, trial, and execution - Smith, Mark D. (Lutterworth Press, 2018)
"Mark Smith brings his experience as a classical historian to bear on the life of the historical Jesus, piecing together the volatile political context of first-century Judaea, as well as the lives of Pontius Pilate, Annas, and Joseph Caiaphas. The claim that 'the Jews crucified Jesus' has spawned a long and tragic history of Christian anti-Semitism. Smith challenges this claim through detailed exploration of Roman, Jewish, and Christian written sources and a broad range of archaeological evidence, such as the ossuary of Caiaphas, the 'Hidden Gate', and the rich vein of research devoted to the archaeology of ritual purity. The result is an earthy and nuanced portrait of Jewish life under Roman rule. From his discussion of the multiplicity and brutality of Roman executions to the intricate personal relationships among elites that provided the means of collaboration and redress, Smith details the complex push-pull of forces between Rome and the Temple as they collided in one history-changing week."--Publisher description